Assessing Study Skill Needs for Information Technology and Computer Science Students in Technical and Vocational Universities - Yi-Fang Lee; James W. Altschuld; Pi-Kuang Tseng; Hsinling Sonya Hung (Heliyon, 2023)
Not a great deal is known about what study skills are essential for success in the science, technology, engineering, and mathematics' disciplines, particularly in information technology (IT) and computer science (CS) programs in the technical and vocational education (TVE) in Taiwanese higher education. Since TVE accounts for more than half of the post-secondary enrolments in the country, and with the increasing demand for IT and CS talents, we studied perceptions of the importance and competency of such skills to identify the students’ needs and demographic factors influencing them. A survey was administered to 1398 students in IT and CS programs in Taiwanese TVE universities. General skills were seen as the most important one among the study skills examined, and students felt competent using them. The needs to manage time, perform quantitative/mathematical tasks, and delegate were identified and these needs were affected by institutional quality, gender, and academic achievement. The results might be useful for further investigation in this area and guiding future plan to improve student performance in TVE.